Status kebersihan gigi dan mulut Suku Papua pengunyah pinang di Manado Oral and dental hygiene status of Papua’s Areca nut chewer - Krista Veronica Siagian (Journal of Dentomaxillofacial Science, 2012)
Areca nut chewing habits is one of the greatest threats to oral health today. It is estimated that 600 million peoplehave areca nut chewing habit, including Papua ethnic group. The purpose of this study was to evaluate the oralhygiene status of Papua ethnic group who have areca nut chewing habits living in at Manado. The study is adescriptive cross sectional type using survey technique. Thirty respondents, males and females aged between 18 to40 years old were collected as purposive sample. Clinical data of oral hygiene status was assesed by OHI-S IndexGreene and Vermillion, including debris and calculus score. Results indicated that oral hygiene score (OHI-S)is2.32. The conclusion of this study is the oral hygiene status of Papua’s areca nut chewers living in at Manado, ismedium category.